Data from: Experimental herbivore exclusion, shrub introduction, and carbon sequestration in alpine plant communities ... - Sørensen, Mia Vedel; Graae, Bente Jessen; Hagen, Dagmar; Enquist, Brian Joseph; Nystuen, Kristin Odden; Strimbeck, Richard (Dryad, 2018)
Background: Shrub cover in arctic and alpine ecosystems has increased in recent decades, and is predicted to further increase with climate change. Changes in shrub abundance may alter ecosystem carbon (C) sequestration and storage, with potential positive feedback on global C cycling. Small and large herbivores may reduce shrub expansion and thereby counteract the positive feedback on C cycling, but herbivore pressures have also changed in the alpine-arctic tundra; the increased shrub cover together with changes in herbivore pressure is leading to unpredictable changes in carbon sequestration and storage. In this study we investigate the importance of herbivory and shrub introduction for carbon sequestration in the short term. We measured standing biomass and daytime mid-growing season carbon fluxes in plots in a full factorial design where we excluded small and large mammalian herbivores and introduced Salix by planting Salix transplants. We used three study sites: one Empetrum-dominated heath, one herb- ... : CO2 fluxes and biomass during experimental herbivore exclusion and shrub introductionField data of CO2 fluxes (including Net Ecosystem Exchange, Ecosystem Respiration and Gross Ecosystem Photosynthesis) and the environment (such as light, moisture, and air, surface, and soil temperature) during measurements and vegetation data (including absolute abundance and measured and estimated biomass of functional groups). Methods and experimental design is explained in publication. The data is processed in R core Team 2017.Data_fluxes_and_biomass_BMC_Ecology_Dryad.xlsx ...